2013
DOI: 10.1080/0907676x.2013.831919
|View full text |Cite
|
Sign up to set email alerts
|

Phrasal verbs in Italian dubbed dialogues: a multimedia corpus-based study

Abstract: The presence of colloquialisms, set phrases and idioms has often been investigated in AVT studies as a gauge for determining the levels of naturalness and verisimilitude of original film and dubbed dialogues compared to naturally-occurring speech. Up until recently, however, the results of these studies have almost exclusively been based on the analysis of transcribed film data. It will be the aim of this study to explore the frequency of use of a specific linguistic trait of colloquial Italian, i.e. phrasal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Minutella argued that interference may sometimes originate from the need to respect lip-synchronization constraints. In a similar vein, Valentini (2013) provided examples of verb-particle contractions in Italian films dubbed from French which are calqued on their source counterparts, for reasons of isochrony. Pavesi (1994, p. 137) and subsequently Rossi (2006, p. 310) observed that the English post-utterance question tag in original film versions "will you?"…”
Section: Synchronization Issues In Avt Studiesmentioning
confidence: 94%
“…Minutella argued that interference may sometimes originate from the need to respect lip-synchronization constraints. In a similar vein, Valentini (2013) provided examples of verb-particle contractions in Italian films dubbed from French which are calqued on their source counterparts, for reasons of isochrony. Pavesi (1994, p. 137) and subsequently Rossi (2006, p. 310) observed that the English post-utterance question tag in original film versions "will you?"…”
Section: Synchronization Issues In Avt Studiesmentioning
confidence: 94%
“…Corpus linguistics has been used to study audiovisual translations with diverging approaches in terms of scope and data processing. A prototypical example is the Forlì Corpus of Screen Translation (Heiss and Soffritti, 2008;Valentini, 2008Valentini, , 2013, an electronic database of original films and TV series, and their dubbed and subtitled versions in different languages (Chinese, Dutch, French, German, and Italian).…”
Section: Corpus Studies and Audiovisual Translationmentioning
confidence: 99%
“…Moreover, other scholars also discussed fruitful benefits of collocation beyond its language advantages in the artwork, such as movies and representation of things and individuals. Empirical literature scrutinizes the collocation of the movie's dubbing translation of American and British movies to Italian (Freddi, 2013) and French to Italian (Valentini, 2013). Further, collocation is also functioned to make representation.…”
Section: Introductionmentioning
confidence: 99%